Teaching english through fairytales - Rajapova, Malika; Sheraliyeva, Nodirakhon (Результаты научных исследований в условиях пандемии (COVID-19), 2022)
This article describes how literature is connected with teaching foreign languages, particularly fairy tales promote improving all language skills. It gives useful information on choosing the right tales according to the audience. The article emphasizes the importance and the role of fairy tales in teaching English